Gender differences in computer mediated communication environment: a study on UPM students' responses in an online writing forum / Nuramira Anuar - Anuar, Nuramira (2011)
The technology has greatly benefited our lives in many ways. In education, computer mediated communication is now integrated in teaching and learning. The purpose of this study is to examine the differences of the linguistic and autographic features used between male and female students of Universiti Putra Malaysia (UPM) in the Online Writing Forum. The instrumentation used to facilitate the present study is UPM Online Writing Forum. The students’ writings in the forum were analyzed and discussed and further compared to previous research. The results of the research revealed that females tend to use more pronouns that show relationship with the readers than males. Females also tend to use boosters more in their writings rather than males. In contrast, males tend to hedge slightly more than females in their writings. For autographic feature differences, females tend to make more mistakes in the use of upper and lower cases in their writings, and they also use more emoticons in their posts in the Online Writing Forum. These findings could be useful to language instructors and curriculum implemented in understanding the language and autographic features differences between males and females in computer-mediated-communication environment. Further studies should be carried out to investigate other linguistic and autographic features differences between males and females when interacting in Online Writing Forums.